Effect of electrolytic lesion of the dorsal raphe nucleus on water intake and sodium appetite - Olivares,E.L. (2003)
The present study determined the effect of an electrolytic lesion of the dorsal raphe nucleus (DRN) on water intake and sodium appetite. Male Wistar rats weighing 290-320 g with a lesion of the DRN (L-DRN), performed two days before experiments and confirmed by histology at the end of the experiments, presented increased sensitivity to the dehydration induced by fluid deprivation. The cumulative water intake of L-DRN rats reached 23.3 ± 1.9 ml (a 79% increase, N = 9) while sham-lesioned rats (SL-DRN) did not exceed 13.0 ± 1.0 ml (N = 11, P < 0.0001) after 5 h. The L-DRN rats treated with isoproterenol (300 µg kg-1 ml-1, sc) exhibited an increase in water intake that persisted throughout the experimental period (L-DRN, 15.7 ± 1.47 ml, N = 9 vs SL-DRN, 9.3 ± 1.8 ml, N = 11, P < 0.05). The L-DRN rats also showed an increased spontaneous sodium appetite during the entire period of assessment. The intake of 0.3 M NaCl after 12, 24, 36 and 72 h by the L-DRN rats was always higher than 20.2 ± 4.45 ml (N = 10), while the intake by SL-DRN was always lower than 2.45 ± 0.86 ml (N = 10, P < 0.00001). Sodium- and water-depleted L-DRN rats also exhibited an increased sodium appetite (13.9 ± 2.0 ml, N = 11) compared to SL-DRN (4.6 ± 0.64 ml, N = 11) after 120 min of observation (P < 0.02). The sodium preference of L-DRN rats in both conditions was always higher than that of SL-DRN rats. These results suggest that electrolytic lesion of the DRN overcomes a tonic inhibitory component of sodium appetite.